Economics in action : an applications book - Cameron, Beverly J.; Cameron, Norman E. (New York : St. Martin's Press, 1984)
The text explained theoretical tools such as demand and supply, micro and macro economics as well as other economic systems.
Includes index.
kjo 17/01/2019
Loans
Keywords: Economics